SHOCK METAMORPHISM OF SOME ROCK-FORMING MINERALS: EXPERIMENTAL RESULTS AND NATURAL OBSERVATIONS - Fel'dman V.I.; Sazonova L.V.; Kozlov E.A. (My University, 2006)
The products of shock metamorphism in the Jänisjärvi astrobleme in Karelia, Russia, are compared with the results of experiments in which spherical converging shock waves affected a spherical rock sample. The sample was loaded by a broad spectrum of shock pressures, which increased from >20 GPa at the periphery of the rock sphere to > 200 GPa at its center. Experiments with rocks metamorphosed under the effect of spherical converging shock waves imitate collisions of cosmic bodies with the Earth's surface, when transformations in rocks and minerals are induced by a single impact event. The shock-thermal decomposition of mafic minerals occurs in the same succession in nature and the experiments, with some differences between natural and experimentally produced shock-thermal aggregates likely accounted for by the smaller sizes of the experimental impact rock sample and, correspondingly, its more rapid quenching. Our shock experiments were the first to synthesize ringwoodite that was rich in Al2O3 and should be referred to as aluminous ringwoodite. The mineral was produced not via the martensite transition of olivine but by means of biotite replacement coupled with the migration of elements. The transformations of minerals by shock waves (amorphization and shock-thermal decomposition) were determined to be controlled mainly by the crystal structures of these minerals. The experimental products provide evidence of the migration of chemical elements within the crystal structure. The structural setting of ions in a mineral determines the onset of element migrations and the intensity of this process. © Nauka/Interperiodica 2006.